PEMIKIRAN ISMÃIL RÃJI AL-FARÃQÃ (1921-1986) TENTANG ISLAMISASI SAINS DAN PENGARUHNYA TERHADAP PENGEMBANGAN DASAR-DASAR FILOSOFIS PENDIDIKAN ISLAM - Abidin, Zainal (P3M STAIN Jurai Siwo Metro, 2011)
AbstractIslamization of knowledge or islamization of sciences is the great issues of the earlyÂ transformation Islamic thought after the revivalist Islamic thinker. This era can be called as the most popular at the early yearsÂ ofÂ 1980 and became the biggest orientation of muslim activist who isÂ concentration of Islamic Thinking,Â Â for examples IsmÃ¢il RÃ¢ji al-FarÃ»qÃ®. He wasÂ introduced the concept about Islamization of knowledge. It is the controversial idea,Â and until now his concept calledÂ as the uthopic idea. But on the reality, some Muslim scholars Â still sure that idea was going and progress for make the ideal Islamic world, especially on the Islamic building of fundamental philosophy in Islamic education.IsmÃ¢il RÃ¢ji al-FarÃ»qÃ® was the established tinker of the world. He very confidence people to make some concept about the tipology of Islamic resurgence. His especially focus on the development in Islamic movement and suggest his works in the trend of Islamization of Knowledge. The implication of Islamization of sciences, actually caused the critical concept with any polemic between another muslim thinker in contemporary era or modern era. And the another side, the Islamization of KnowledgeÂ was introduced by IsmÃ¢il RÃ¢ji al-FarÃ»qÃ® make any influence for concept expecially for developed the basic of Islamic education philosophy.Keyword: Islamization of Knowledge, Islamization of Sciences and The Islamic Fundamental Thougt